Efficacy and safety data for the Ab interno XEN45 gel stent implant at 3 Years: A retrospective analysis. Issue 2 (March 2022) - Gabbay, Itay E; Goldberg, Mordechai; Allen, Felicity; Lin, Zhiheng; Morley, Christine; Pearsall, Tahmina; Muraleedharan, Veena; Ruben, Simon
Purpose: To report efficacy and safety measures of the XEN45 gel stent at 36 months in the UK National Health Service setting. Methods: Retrospective non-comparative audit of the records of patients who underwent XEN45 implantation between June 2015 and May 2017 was performed. Main outcome measures were intraocular pressure and number of antihypertensive medications used. Failure was defined as need for further surgery or stent removal. Success was defined as a 20% decrease in intraocular pressure without the need for additional glaucoma medications or a reduction in antihypertensive medications without an increase in baseline intraocular pressure. Needling rates and preoperative factors effect were assessed. Results: The cohort included 205 patients (205 eyes) with primary open angle glaucoma (84.4%), angle closure glaucoma (7.8%), or refractory glaucoma (7.8%), 62.9% had a stand-alone procedure and 37.1%, a combined phaco-XEN45 procedure. Mean intraocular pressure was 22.6 ± 7.0 mmHg at baseline compared to 14.7 ± 3.8 mmHg at 24 months and 14.0 ± 2.9 mmHg at 36 months ( p < 0.001 for both). Mean number of medications used was 2.6 ± 1.1 at baseline compared to 0.5 ± 0.9 and 0.6 ± 1.0, at 24- and 36-months, respectively ( p < 0.001 for both). The failure rate at 36 months was 25%. Needling was required in 36.6%. Evaluation of background factors yielded an increased failure rate in non-Caucasians compared to Caucasians (74% vs 21%, p < 0.001). Conclusion: XEN45 implantation is effective and safe at 36 months' follow-up. Patients should be advised regarding the risk of failure and possible need for bleb revisions. Careful patient selection may be required.